A argumentação na perspectiva da análise do discurso - Batista, Mônica Aparecida (2011)
Parting from a discursive perspective, considering the subject someone that subjects itself through the language on the speech and that thinks to be the origin of its words, when retakes words already expressed in other speeches a subject affected by the history and ideology we searched in this study, by gestures interpretation, observe how it is build the argumentation on the graduating students from First School. Firstly, we visited the Language Argumentation Theory, and on the sequence, the Enunciation Theory, but we are guided by the Speech Analyzes Theory of a French line founded on Pêcheux, how it is been developed in Brazil. As teacher, we understand that the speech should not be analyzed only parting from a linguistic structure, or even from an I here, right now that control its speech. So, we analyzed how it works the argumentation by the Speech Analyzes perspective, aiming to investigate linguistics marks left by the students on intend to point the different subject-positions and the possible sense effects from the discursive function of the presented arguments. The theoretical concepts are applied to a discursive corpus that was build from the present regularities on the students texts, where the personification through the linguistic mark we came up; the indetermination/impersonality from the use of the third person and indefinite pronouns; the discursive heterogeneous. For a discursive functioning that we understand as a fault of the subject between including itself or not on the responsibilities and/or solutions, we studied the enouncement separately, attesting the difference by the heterogeneous onto a same subject-position. All this regularities point to a fragmented subject that producing its argumentation retake things already said brought by the ideology and crossed by the unconscious, reproducing knowledge